On the genealogy of morality - Nietzsche, Friedrich Wilhelm (Cambridge University Press, 1994)
A Genealogy of Morality is Nietzsche's most important work on morality. A polemical contribution to moral and political theory, it traces the history of concepts such as guilt, responsibility, and justice, offering insight into Nietzsche's assessment of modern times as the epoch of nihilism. This volume contains new translations of the Genealogy and The Greek State and sections from other of Nietzsche's work to which he refers within it (Human All Too Human, Daybreak, The Joyful Science, and Beyond Good and Evil).